2014
DOI: 10.1021/es405118y
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of the Risks to Water Resources from Unconventional Shale Gas Development and Hydraulic Fracturing in the United States

Abstract: The rapid rise of shale gas development through horizontal drilling and high volume hydraulic fracturing has expanded the extraction of hydrocarbon resources in the U.S. The rise of shale gas development has triggered an intense public debate regarding the potential environmental and human health effects from hydraulic fracturing. This paper provides a critical review of the potential risks that shale gas operations pose to water resources, with an emphasis on case studies mostly from the U.S. Four potential r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
907
1
15

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,312 publications
(929 citation statements)
references
References 130 publications
6
907
1
15
Order By: Relevance
“…On the other hand, surface contamination is generally caused by spills, leaks, and accidental releases. Vidic et al [55] and Vengosh et al [56] found little evidence of shallow-water chemical contamination; strong evidence of methane contamination; some evidence of deepwater-shallow-water aquifer mixing; and significant issues regarding produced water management and accidental spills [31].…”
Section: Water Impacts and Issuesmentioning
confidence: 99%
“…On the other hand, surface contamination is generally caused by spills, leaks, and accidental releases. Vidic et al [55] and Vengosh et al [56] found little evidence of shallow-water chemical contamination; strong evidence of methane contamination; some evidence of deepwater-shallow-water aquifer mixing; and significant issues regarding produced water management and accidental spills [31].…”
Section: Water Impacts and Issuesmentioning
confidence: 99%
“…103 For instance, radium has been found to be building up in rivers downstream of shale gas waste discharge points in Pennsylvania, 104 while a company has been fined for contaminating an aquifer with CBM (termed coal seam gas (CSG) in Australia) waste containing uranium in New South Wales, Australia. 105 Summarising much of the data, a recent landmark US study by Vengosh et al argues that the overall risks posed by fracking development for water are fourfold (a similar, though subtly different list could be produced for CBM 106 extraction) 107 :…”
Section: Watermentioning
confidence: 99%
“…They may pose a threat to surface and near surface groundwater as the liners can leak. [78,79] Improper construction or site restoration can result in erosion and sedimentation and an increase in the suspended solid load in streams. [80] Impoundments holding recycling fluids can be a source of VOCs as they are often aerated to keep the growth of bacteria and the resulting sepsis to a minimum.…”
Section: Flowback and Produced Watermentioning
confidence: 99%